Watertightness of wound closure in lumbar spine—a comparison of different techniques - Suter, Aline; Spirig, José Miguel; Fornaciari, Paolo; Bachmann, Elias; Götschi, Tobias; Klein, Karina; Farshad, Mazda (Journal of Spine Surgery; Vol 5, No 3 (September 29, 2019): Journal of Spine Surgery, 2019)
Background: Since a primary watertight dural suture after incidental durotomies has a failure rate of 5–10%, a watertight closure technique of the overlying layers (fascia, subcutis and skin) is essential. The purpose of this cadaveric study was to find the most watertight closure technique for fascia, subcutis and skin. Methods: Different suturing techniques were tested for each layer in a sheep cadaveric model by measuring the leakage pressure. The specimens were mounted on a pressure chamber connected to a manometer and a water tube system. Subsequently, the leakage was over-sewed with a cross stitch and the experiment was repeated. Results: Cross stitch suturing [median =180 mbar (43; 660)] performed best compared to continuous [median =16 mbar (6; 52)] (P=0.003) but not to single knot [median =118 mbar (21; 387)] (P=1.0) or locking stitch suturing [median =109 mbar (3; 149)] (P=0.93) for fascia closure. Continuous suture [median = 9 mbar (3; 14)] resulted in a higher leakage pressure than single knot [median =1 mbar (1; 6)] (P=0.017) for subcutaneous closure. No significant differences were found between intracutaneous, Donati-continuous, single knot and locking stitch for skin closures (P=0.075). However, the Donati-continuous stitch closure resulted in higher pressures in tendency. Over-sewing increased median leakage pressure from 8.0 to 11.0 mbar (P=0.068) and from 4.0 to 13.0 mbar (P=0.042) for single knot and for locking stitch skin closures, respectively. Conclusions: Cross stitches for the fascia, continuous suturing technique for the subcutis and Donati-continuous stitch for the skin resulted in the most watertight closure within this experimental setting. If leakage occurs, over-sewing might relevantly improve the watertightness of the wound.